Pertimbangan Hakim dalam Memutuskan Perkara Kasus Pindana Korupsi di Kota Blitar - Agnes Levina Sesa; Paskah Febiola Dwi Gonstary; Kahfian Yunita Maulidia (UNES Law Review, 2024)
Corruption is a serious crime that harms the nation both financially and morally. This study attempts to highlight a case of corruption committed by a bank teller in Blitar City, involving numerous government officials. In the context of the case faced, one of the defendants, Evi Sulistia Watiningsih, acted as a teller at PD. BPR Artha Praja, Blitar City. This research uses a normative legal analysis method with a case study approach. The result of this study is that the defendant, Evi Sulistia Ningsih, was found guilty of committing corruption in collaboration with others, and was sentenced by the judge to four (4) years in prison and fined 100,000,000 rupiahs with an additional punishment if the fine is not paid. The punishment given by the judge is in accordance with Law No. 20 of 2001 concerning corruption (tipikor), and it is hoped that it will serve as a lesson for the defendant not to commit the same act in the future, which would harm the nation's finances